Surgical Complications of Intracranial Multimodality Monitoring for Neurocritical Care: A Single-center Experience. (16th November 2020) - Barrit, Sami; Schuind, Sophie; Al Barajraji, Mejdi; André, Joachim; Bogossian, Elisa; Taccone, Fabio; Gaspard, Nicolas; De Witte, Olivier J
Abstract: INTRODUCTION: The major disease burden caused by acute brain injuries prompts neurocritical caregivers to investigate the underlying pathophysiological processes of the so-called primary and secondary brain insults in the hope of developing specific monitoring tools and subsequent targeted therapeutic interventions. METHODS: This retrospective study included all patients undergoing iMMM indicated for subarachnoid hemorrhage, traumatic brain injury, and/or intracranial hemorrhage, at a single European center between July 2016 and January 2020. Brain tissue oxygenation probe, semicontinuous microdialysis sensor, and 8 contacts depth electrode constituted iMMM and were inserted using a triple lumen introducer kit (Integra LifeSciences, Plainsboro, NJ) through a burr hole made by a dedicated twist drill bit at Kocher's point, targetting normal-appearing non-eloquent brain area. External ventricular drain or intraparenchymal intracranial pressure monitoring were inserted through a distinct burr hole and their associated complications not considered. Medical records were consulted to retrieve surgical complications directly associated with the insertion of iMMM and defined as: misplacement; hemorrhage; bone fragments and infection. A review of postoperative imaging was performed blinded to the clinical features by an independent radiologist. Institutional review board was obtained. RESULTS: 112 patients, of which 4 pediatric cases, were included in the study for a total of 115 iMMM insertions. 19 patients were concerned by iMMM misplacement as 9 intraventricular, 6 extra-axial and 4 off-target tip position. 12 patients presented hemorrhagic complications, consisting of 9 tract hemorrhages, 3 extradural hematomas, and one subdural hematoma. 5 patients had bone fragments and none infection was retrieved. CONCLUSION: This series of 115 consecutive iMMM insertion reports a complication rate of 16.5% of misplacement, 10.4% of hemorrhagic events, 4.3% of bone fragments and no related infection.